Competencies of dual career support providers (DCSPs): A scenario-specific perspective - Defruyt, S.; Wylleman, P.; Stambulova, N.; Cecic Erpic, S.; Graczyk, M.; De Brandt, K. (International Journal of Sport and Exercise Psychology, 2021)
Although dual career (DC) support is important, there is a lack of research on the competencies professional dual career support providers (DCSPs) themselves require to manage specific job challenges. Therefore, current research, that was part of the Gold in Education and Elite Sport (GEES) project, aims at: (1) examining how well DCSPs managed specific challenges (called scenarios) within the European context, (2) identifying the competencies DCSPs need to manage the scenarios, and (3) exploring which variables influence how well they manage these scenarios. The Dual Career Competency Questionnaire for Support Providers with Scenario extension (DCCQ-SPSc) was completed by 288 DCSPs from nine European countries. The scenarios were: (1) Managing a non-supportive environment, (2) Supporting a student-athlete to cope with relocation, (3) Supporting a student-athlete in developing a study plan, (4) Helping a student-athlete to cope with a challenging year, (5) Referring a student-athlete to other professional help, and (6) Dealing with wrong expectations of a student-athlete. Results revealed that each scenario was experienced by more than half of the DCSPs (range 55%-87%) and that in general, they managed these scenarios average up to good. DCSPs prioritised different competency factors depending on the specific scenario. Frequency of experiencing (for the first four scenarios) and possession of the prioritised competency factor (for all scenarios) were significant predictors for the management of the scenarios. This study shows the importance of scenario-specific competency development and can be used in the development of educational curricula for DCSPs.